Environmental risks outweigh dopaminergic genetic risks for alcohol use and abuse from adolescence through early adulthood. (1st June 2017) - Coley, Rebekah Levine; Sims, Jacqueline; Carrano, Jennifer
Highlights: Assessed alcohol use behaviors from adolescence through early adulthood. A dopamine-system genetic risk score was linked with growth of intoxication rates. The genetic risk score was not linked with other alcohol use behaviors. Stressful life events and social norms predicted heightened alcohol use behaviors. No evidence of gene-environment interactions emerged. Abstract: Background: Alcohol use is a primary public health concern, particularly among adolescents and young adults. Based on the rapidly growing field of gene-environment models, this study assessed the combined role of environmental and dopamine-related genetic correlates of early alcohol use and abuse. Methods: Multilevel growth models assessed trajectories of alcohol use and intoxication and ordered logistic regressions assessed alcohol use disorder among a sample of 12, 437 youth from the nationally representative Add Health study who were followed from mid-adolescence through early adulthood. Results: Endogenous and exogenous stressful life events and social norms supportive of alcohol use from parents and peers were significant predictors of alcohol use, intoxication, and alcohol use disorder, with consistent patterns across males and females. In contrast, a dopamine-system genetic risk score (GRS) was not associated with alcohol use trajectories nor alcohol use disorder in early adulthood, although weak connections emerged between the GRS and growth trajectories of intoxication, indicating that higher GRS predicted more frequent episodes of intoxication during the transition to adulthood but not during adolescence or later 20s. No evidence of gene-environment interactions emerged. Conclusions: Results extend a substantial body of prior research primarily assessing single genetic polymorphisms in the dopamine system, suggesting that dopaminergic GRSs may be associated with more problematic alcohol behaviors at some developmental periods, but further, that social norms and stressful life experiences are more consistent correlates of early and problematic alcohol use among youth. These environmental factors present potential targets for research manipulating contexts to identify causal pathways.